FUZZY SYSTEM AS FOUR-JOINT ROBOT MOVEMENT CONTROL FOR MOVING GOODS BASED ON TIME AND OBJECT COLOR - Emmanuel Agung Nugroho; Nanang Roni Wibowo; Afzeri; Riqqi Rizalludin; Marwan Ruswanda (LPPM Politeknik Enjinering Indorama, 2022)
Technology Disruption has driven the acceleration of the industrial era 4.0 which is based on thespeed of data-based systems and artificial intelligence. Another impact is intelligent robots as asubstitute for human performance, because humans experience fatigue and decrease accuracywith increasing working time. Robots are an alternative whose presence cannot be avoided,therefore the robot's work system must be improved to optimize its speed and accuracy. One ofthe implementations of the robot is as a product moving machine from the initial coordinates (Pick)to the destination coordinates (Place). This study uses a four-joint robot (4 DOF) with a producttransfer mechanism that can be adjusted based on the input priority that has been set using theFuzzy Logic Control (FLC) method which is implemented using an Arduino Mega 2560microcontroller, and the robot used is Dobot Magician. There are 2 input variables used, namelythe mass of the object detected by the Weight sensor Load Cell + HX711 module and the colorof the object detected using the TCS3200 color sensor. The output variable is the movement ofthe robot to the Place which can be analyzed by calculating the position matrix using the Matlabprogram.